INTERNATIONALIZATION AND FINANCIAL STABILITY OF DEPOSIT MONEY BANKS IN NIGERIA - Chukwuka, Egbule; Akintoye, Rufus Ishola; Aguguom, Theophilus Anaekenwa (International Journal of Accounting & Finance Review, 2023)
This study aims to examine the effect of internationalization on the financial stability of deposit money banks in Nigeria.  The study is crucial, as financial stability is significant in the effective functioning of all other sectors of the Nigerian economy. The data for the study were extracted from the financial statements of the deposit money banks listed on the Nigerian Exchange Group as of 2ist December 2021. The validity and reliability of data were premised on their certification financial statements by statutory auditors. Descriptive and panel data analysis were employed for the data analysis. The findings demonstrate that foreign assets to total assets and foreign taxes to total taxes have insignificant effects, while foreign profits and total profits and cross-border banking activities have significant effects. However, the joint statistics further reveal that internationalization has a positive effect on the financial stability of deposit money banks in Nigeria. The result suggests that managers at the foreign operations of the banks should review operational strategies to ensure adequate support and improve foreign banking operations performance towards contributing to the financial stability of the banks.JEL Classification Codes: G50, P45, F23, B17.